(3GdTaG HJYQja Mbhb GdeUWais - (3GdjMUHj, CHh GdaVd, GdbGVj YjGV, YjGV Hf ehSi Hf YjGV, J(B544(3g`s ((3eMeO Hf GdMGL cHjQ Ydj LGhT CZGs)
(3ChdgG (B:s
(3CHh GdaVd YjGV Hf ehSi Hf YjGV CeG HYO aj eLehY jJVef GdJYQja HbO GdeUWai Udi Gddg Ydjg hSdehJQLeJg HGdTaG HJYQja Mbhb GdeUWais
(3BNQgG (B:s
(3HGSe GdaSb eQGSe Gdabg ajJbOe Edjg aj Pdc hjDNQ hdG JbHd aJhGg hdG TgGOJg hgj LQMI KGHJI ajg hjHZV aj Gddg JYGdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 99s
(3eYLe GdeDdajf(B: 2 / 588s
(3cTa GdXfhf(B: 2 / 1052s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJGQjNs